2019
DOI: 10.3390/biom10010066
|View full text |Cite
|
Sign up to set email alerts
|

The Emerging Role of Long Non-Coding RNAs in the Metastasis of Hepatocellular Carcinoma

Abstract: Long non-coding RNAs (lncRNAs) play multifaceted roles in modulating gene expression under both physiological and pathological processes. The dysregulation of lncRNAs has been increasingly linked with many human diseases, including a plethora of cancers. Mounting evidence indicates that lncRNAs are aberrantly expressed in hepatocellular carcinoma (HCC) and can regulate HCC progression, as well as metastasis. In this review, we summarize the recent findings on the expanding roles of lncRNAs in modulating variou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
40
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
9
1

Relationship

4
6

Authors

Journals

citations
Cited by 72 publications
(41 citation statements)
references
References 86 publications
(104 reference statements)
1
40
0
Order By: Relevance
“…Accumulating evidence indicated that lncRNAs have the signi cant function in the carcinogenesis and the progression of malignancies during these years [23]. Therefore, it's crucial to investigate the regulatory characteristics of lncRNAs in the pathogenesis of HCC.…”
Section: Discussionmentioning
confidence: 99%
“…Accumulating evidence indicated that lncRNAs have the signi cant function in the carcinogenesis and the progression of malignancies during these years [23]. Therefore, it's crucial to investigate the regulatory characteristics of lncRNAs in the pathogenesis of HCC.…”
Section: Discussionmentioning
confidence: 99%
“…The diverse regulatory functions of lncRNAs in various biological processes [ 19 , 20 ] control the expression of genes by different mechanisms [ 21 ]. These mechanisms include acting as decoys (molecular sinks for transcription factors and repressors to facilitate gene activation and silencing), guides (bind to enzymatically active or regulatory protein complexes and lead them to a specific target), scaffolds (act as a central platform to which various protein complexes can tether and lead to specific genomic locations), signaling molecules (associated with specific signaling pathways), and miRNA sponges (modulating miRNA expression) [ 22 ].…”
Section: Lncrnasmentioning
confidence: 99%
“…The invasion of cancer cells into surrounding tissues and vessels is an early stage of tumor metastasis. As more than 90% of cancer patients die due to persistent recurrence, metastasis and chemotherapy resistance, there is a need for studies to prevent or target metastasis [116][117][118][119][120][121][122]. Casticin significantly reduced the cell migration rate by 77.41% after 48 h of 5 µM compared to the control of DU145 cells [99] and inhibited cell migration by 93% after 24 h of 200 nM in human melanoma A375.S2 cancer cells [123].…”
Section: Effect Of Casticin On Metastasismentioning
confidence: 99%